2016
DOI: 10.1007/s40121-016-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ceftaroline Fosamil in Children: Review of Current Knowledge and its Application

Abstract: Ceftaroline is a novel cephalosporin recently approved in children for treatment of acute bacterial skin and soft tissue infections and community-acquired bacterial pneumonia (CABP) caused by methicillin-resistant Staphylococcus aureus, Streptococcus pneumoniae and other susceptible bacteria. With a favorable tolerability profile and efficacy proven in pediatric patients and excellent in vitro activity against resistant Gram-positive and Gram-negative bacteria, ceftaroline may serve as a therapeutic option for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…La vancomicina sigue siendo la primera opción de tratamiento en pacientes con infecciones invasivas por SAMR, pero su toxicidad renal, s u r e d u c i d o e s p e c t r o y l a b a j a concentración que alcanza a nivel tisular justificarían la búsqueda de nuevas alternativas de tratamiento. [1][2][3][4][5] E n 2 0 1 1 , l a S o c i e d a d d e Enfermedades Infecciosas de América recomendó dosis de vancomicina de 15 mg/kg por dosis cada 6 horas p a r a l o s n i ñ o s c o n i n f e c c i o n e s invasivas debidas al SAMR con el objetivo de alcanzar altos niveles de concentración en valle. 1 Esto permitiría que se estableciera un área de vancomicina bajo la curva, que, en los adultos, predecía mejor la eficacia, pero, después de la incorporación de estas recomendaciones, varios autores informaron que, en los pacientes pediátricos, se evidenciaba una asociación entre las dosis mayores de vancomicina y la falla renal.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La vancomicina sigue siendo la primera opción de tratamiento en pacientes con infecciones invasivas por SAMR, pero su toxicidad renal, s u r e d u c i d o e s p e c t r o y l a b a j a concentración que alcanza a nivel tisular justificarían la búsqueda de nuevas alternativas de tratamiento. [1][2][3][4][5] E n 2 0 1 1 , l a S o c i e d a d d e Enfermedades Infecciosas de América recomendó dosis de vancomicina de 15 mg/kg por dosis cada 6 horas p a r a l o s n i ñ o s c o n i n f e c c i o n e s invasivas debidas al SAMR con el objetivo de alcanzar altos niveles de concentración en valle. 1 Esto permitiría que se estableciera un área de vancomicina bajo la curva, que, en los adultos, predecía mejor la eficacia, pero, después de la incorporación de estas recomendaciones, varios autores informaron que, en los pacientes pediátricos, se evidenciaba una asociación entre las dosis mayores de vancomicina y la falla renal.…”
Section: Introductionunclassified
“…2,3 La ceftarolina fosamil es una cefalosporina que ha generado mucho interés como una posible opción de tratamiento. Como es el caso de otras cefalosporinas, la actividad antibacteriana de la ceftarolina es el resultado de la unión a proteínas esenciales que inhibe la síntesis de la [4][5][6][7][8] En Argentina, está aprobado por la Administración Nacional de Medicamentos, Alimentos y Tecnología Médica (ANMAT), pero el prospecto autorizado destaca que no debe utilizarse en niños y adolescentes, ya que no existen datos suficientes en estas poblaciones.…”
Section: Introductionunclassified
“…Vancomycin is still the first-line option for patients with invasive MRSA infections, but its kidney toxicity, its narrow spectrum, and its low tissue level would warrant the search for new therapy options. [1][2][3][4][5] In 2011, the Infectious Diseases Society of America recommended vancomycin in doses of 15 mg/kg every 6 hours for children with invasive MRSA infections in order to reach high trough levels. 1 This would allow to establish a vancomycin area under the curve that, in adults, would better predict effectiveness; however, after these recommendations were i m p l e m e n t e d , s e v e r a l a u t h o r s reported that, in pediatric patients, there was an association between higher vancomycin doses and kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…Ceftaroline has a broad spectrum of activity against clinically relevant Gram-positive strains, including MRSA and resistant Streptococcus pneumoniae strains, as well as Gram-negative pathogens implicated in skin and soft tissue infections (SSTIs) or communityacquired pneumonia (CAP). [4][5][6][7][8] In Argentina, it was approved by the National Drug, Food and Technology Administration of Argentina (Administración Nacional de Medicamentos, Alimentos y Tecnología Médica, ANMAT), although the authorized package insert indicates that it should not be used in children and adolescents because there are not sufficient data in these populations.…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 In addition, the drug has been approved by the FDA for CAP caused by Streptococcus pneumoniae , methicillin-sensitive, Staphylococcus aureus (non-MRSA), Escherichia coli, Haemophilus influenzae, Klebsiella pneumonia , and Klebsiella oxytoca . 1 , 3 5 Nevertheless, data on the clinical use of ceftaroline are scarce, especially in the pediatric population. 5 …”
Section: Introductionmentioning
confidence: 99%